Biological properties of cord blood hematopoietic stem cells - S. A. Rumiantsev; E. Yu. Osipova; S. E. Ipatov; T. V. Shamanskaya; O. A. Mayorova; A. G. Rumyantsev (Онкогематология, 2014)
This article provides an overview of research evolution of umbilical cord blood as a source of hematopoietic stem cells for transplantation. Phased developments of the technology of stem cells detection and selection, their proliferation, differentiation and function assessment using cultivation in vitro and in vivo in animal model was described. Differences of cord blood stem cells in comparison with those from other sources were described. The role of microenvironment for stem cells self-renewal and differentiation is shown. The possibility of stem cells biological properties modeling on example of using a vector based on HIV type 1 containing Notch genes, to regulate CD133+ and CD34+ cord blood stem cells proliferation is shown.